Object-based learning with concept mapping embodied intelligent agent - Goh, Ong Sing; Fung, Chun Che; Depickere, Arnold; Lau, Siong Hoe (2005)
For effective learning, the teaching materials for the learning purpose should be comprehensible and appropriate for the learners. Moreover, the learners are expected to construct the concepts and relations of the learning materials so as to achieve the desired learning objectives. Concept mapping is a technique using graphs for representing knowledge in a structure according to different levels of abstraction and inclusion. The technique has been widely applied in many disciplines and various educational levels. This learning environment is intended to guide the learners toward general understandings of the topic they have to learn. In concept mapping with learning objects settings, learners are able to direct their own unique sequences of tailored instructions under their control. This paper shows how the concept mapping and learning objects can be integrated in the Constructive Learning Model Embodied Intelligent Agent. The authors propose learning objects as a form of resources, concept maps as representation of the instructional tool and intelligent agent as a means to assist learners to create a personalized learning environment.